2020
DOI: 10.1002/cptc.202000163
|View full text |Cite
|
Sign up to set email alerts
|

Photocaged Nanobodies Delivered into Cells for Light Activation of Biological Processes

Abstract: We have recently reported photocaged nanobodies, termed photobodies, that can be light‐activated in their antigen binding properties due to the removal of the photolabile protection group. We aimed to establish the delivery and activation of photobodies inside mammalian cells, because intracellular protein manipulation and detection by using antibodies and antibody fragments like nanobodies is highly attractive, however, the spatial and temporal control of their application in cells is extremely limited. AntiG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…We show that this switch in binding affinity is in a useful range for cell culture experiments when addressing the ALFA‐tag as an extracellular epitope. Although not reported here, we and others have previously demonstrated that nanobodies photocaged with the same chemistry of the ONBY‐approach can be activated when binding to or when being located inside mammalian cells, by directly irradiating the cells for a few seconds, thus suggesting the same to be feasible for the ALFA‐Pb [2,3b,25] . The ALFA‐Pb represents the sixth example of a successful photobody design that so far only required a properly positioned tyrosine in the paratope region, thereby underlining the simplicity and generality of the approach.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We show that this switch in binding affinity is in a useful range for cell culture experiments when addressing the ALFA‐tag as an extracellular epitope. Although not reported here, we and others have previously demonstrated that nanobodies photocaged with the same chemistry of the ONBY‐approach can be activated when binding to or when being located inside mammalian cells, by directly irradiating the cells for a few seconds, thus suggesting the same to be feasible for the ALFA‐Pb [2,3b,25] . The ALFA‐Pb represents the sixth example of a successful photobody design that so far only required a properly positioned tyrosine in the paratope region, thereby underlining the simplicity and generality of the approach.…”
Section: Discussionmentioning
confidence: 77%
“…Tyr42 is oriented towards Arg11 of the ALFA‐tag (Figure 1B). Despite this seemingly well‐defined molecular contact, Tyr42 sits rather on the edge of the paratope‐epitope interface, much less centrally located than tyrosine positions in other nanobodies that we had previously exploited for the design of photobodies [2,3b] . Whether such a molecular arrangement with Tyr42 replaced by ONBY would still give rise to a sufficiently strong deactivation effect appeared as a challenging test for the generality of our photobody design strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Photochemical disruption of endosomal membranes has been combined with bioinspired reagents like peptides and lipid-based, polymer-based and also inorganic carriers [ 126 129 , 133 136 ] and has also been used to deliver proteins [ 130 , 137 ]. The combination of inorganic glass beads with mechanical “hitting” to deliver photocaged antibodies into cells has also been described [ 138 ].…”
Section: Carriersmentioning
confidence: 99%
“…Intracellular use of photo‐caged nanobodies was first shown by delivering purified photocaged nanobodies synthesised in E. coli to HeLa cells expressing the antigen, [35] and subsequently by directly expressing a photo‐caged nanobody in a cultured human cell line [36,37] …”
Section: Introductionmentioning
confidence: 99%